PENINGKATAN KAPASITAS KARANG TARUNA DALAM MENDUKUNG CAPAIAN PROGRAM FAST TRACK HIV-AIDS - Wiwin Martiningsih; Sri Winarni (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
ABSTRACT The achievement of getting 3 zeros target of HIV-AIDS Program (zero new infection, zero related death, and zero discrimination) in 2021 at Blitar city is still far from expectations, because HIV cases still increasing, even at the age of teenagers. This Community Service is the implementation of the “Suluh” program with the target of teenagers, which aims to involve teenagers in HIV AIDS prevention, suppressed new HIV patients, especially teenagers, and support other 3 zero programs. The activity was carried out with the target of teenagers in 7 villages, Sananwetan Subdistrict, Blitar City in July 2022. The activity carried out was to train teenagers to be able to provide education in their village through TikTok video education media and making banners with the theme of HIV AIDS prevention. The results of this activity were: 1) ) Teenagers' understanding of HIV material was quite good, indicated by 94% answering quite clearly, but in making TikTok videos 82% were less clear, while the banner making was only 10% unclear, 2) Seven banners with different themes that have been installed in strategic places in their villages, and 3) Seven TikTok videos have been distributed through Whatsapp groups of teenagers and WPA (Warga Peduli AIDS). One of the obstacles in making educational media was the cooperation that has not been maximized between teenagers and WPA because difficult suited the learning activities at school. Hereafter, it is hoped that there will be a continuation of activities involving teenagers through scheduling and self-motivation of the teenagers.Keywords: teenagers; Suluh program; HIV-AIDS ABSTRAK Pencapaian target getting 3 zero of HIV AIDS Program (zero new infection, zero related death, dan zero discrimination) pada tahun 2021 dikota Blitar masih jauh dari harapan, hal ini ditandai dengan terus bertambahnya kasus HIV bahkan pada usia remaja.  Pengabdian Masyarakat ini merupakan pelaksanaan program Suluh dengan sasaran remaja yang bertujuan untuk melibatkan remaja dalam pencegahan HIV AIDS, menekan pasien baru HIV terutama pada remaja, dan mendukung program 3 zero lainnya. Kegiatan dilaksanakan dengan sasaran remaja di di 7 Kelurahan Kecamatan Sananwetan Kota Blitar pada bulan Juli 2022. Kegiatan yang dilakukan adalah melatih remaja agar dapat memberikan edukasi dilingkungannya melalui media edukasi video TikTok dan pembuatan banner yang bertemakan pencegahan HIV AIDS. Hasil dari kegiatan ini adalah: 1) ) Pemahaman remaja tentang materi HIV cukup baik ditunjukkan dengan 94% menjawab cukup jelas, namun dalam pembuatan video tiktok 82% kurang jelas, sedangkan pemahaman tentang pembuatan banner hanya 10% yang kurang jelas, 2) Tujuh banner dengan tema yang berbeda telah terpasang ditempat-tempat yang strategis dilingkungan masing-masing, dan 3) Tujuh  video tik tok telah disebarkan melalui WA group remaja dan WPA (Warga Peduli AIDS). Hambatan dalam pembuatan media edukasi salah satunya adalah kerjasama yang belum maksimal antara remaja dan WPA karena adanya kegiatan pembelajaran di sekolah. Diharapkan adanya keberlanjutan kegiatan yang melibatkan remaja melalui pengaturan jadwal dan motivasi diri dari remaja.Kata Kunci: remaja; program suluh; HIV-AIDS